2020
DOI: 10.18203/2349-3291.ijcp20204410
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for retinopathy of prematurity at a medical college hospital in rural Tamil Nadu, India

Abstract: Background: The objective of the research was to evaluate the incidence of retinopathy of prematurity (ROP), association of prenatal and postnatal risk factors, pattern of ROP and treatment outcomes among infants admitted to neonatal intensive care unit (NICU) of tertiary care center located in Thiruvannamalai, Tamil Nadu.Methods: A retrospective study done in all infants admitted between April 2019 and March 2020 who met the criteria for ROP screening with gestational age (GA) less than or equal to 36 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One individual study suggested incidence of ROP in China as 18.5%, one Indian paper reported incidence of 33%, in Pakistan two publications reported 24.6% and 32.4% incidence. [9][10][11][12] One previously done study conducted in Aga Khan University Hospital Karachi evaluated the neonates by extending the screening criteria to 35 weeks of gestation and weight to 2000 gm and showed incidence of 9%. 13 In addition, a recent study from Lahore, Pakistan reported the frequency of ROP in 21% of the neonates.…”
Section: Discussionmentioning
confidence: 99%
“…One individual study suggested incidence of ROP in China as 18.5%, one Indian paper reported incidence of 33%, in Pakistan two publications reported 24.6% and 32.4% incidence. [9][10][11][12] One previously done study conducted in Aga Khan University Hospital Karachi evaluated the neonates by extending the screening criteria to 35 weeks of gestation and weight to 2000 gm and showed incidence of 9%. 13 In addition, a recent study from Lahore, Pakistan reported the frequency of ROP in 21% of the neonates.…”
Section: Discussionmentioning
confidence: 99%